Analysis of critical thinking disposition of prospective islamic elementary school teachers based on self-confidence - Wibowo, Djoko Rohadi; Husni, Miftahul; Shawmi, Ayu Nur; Jadidah, Ines Tasya (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2025)
This study aims to uncover the relationship between the confidence and critical thinking skills of prospective MI/SD teachers and their impact on their teaching quality. This lack of understanding is a significant problem because critical thinking skills are indispensable to overcoming the challenges of the increasingly complex world of education. This research focuses on how self-confidence can shape the critical thinking skills of prospective teachers and their relevance to better teaching. This study involved 50 prospective MI/SD teachers who were registered in the MI/SD Teacher Education Program of Raden Intan State Islamic University Lampung. The qualitative approach was chosen because it allows us to delve deeper into the subjective experience of prospective teachers regarding how they use confidence to improve their critical thinking skills. This approach is appropriate because it provides space for a more holistic understanding of individual experiences and perceptions in the context of learning. The methods used qualitatively include open interviews, documentation, and observation, with data analysis following the Miles, Huberman, and Saldana models. The results of the study show that high self-confidence strengthens critical thinking skills through good material preparation, effective teaching strategies, and a supportive environment. For example, prospective teachers who were initially hesitant are now more confident in asking analytical questions to students. This study recommends educational institutions design training programs to increase the confidence of prospective teachers to be ready to face educational challenges and improve the quality of teaching.